Contemporary editing - Cecilia, Friend (McGraw-Hill, 2005)
Today's news media are increasingly affected by the emergence of electronics and interactive technology and the quickening pace of contemporary life. Yet the time-honored skills of copy editing and news judgment are still necessary. News professionals of the future need a combination of emerging and traditional skills to prepare themselves for editing in the 21st century. "Contemporary Editing" is the definitive text to equip your students with both the basic skills of effective publications editing, and the context to deal with the changing nature of the print medium and news forums. Each chapter opens with an overview and ends with a summary of the topics covered in the chapter. Boxes highlight important points, while step-by-step editing helps students think critically about making editorial decisions and news judgements. Profiles of industry professionals give students the inside scoop on successful journalists. Photos, illustrations, graphs, and sample articles add to the lively writing and visual appeal of the book